Technological Transition and the New Skills Required by the Agribusiness Sector - Baptista, Renato Dias (Int Food & Agribusiness Management Review, 2012)
Adoption of new technologies throughout the agribusiness chain is necessary to meet the higher food and fuel needs of a growing and wealthier population. However, modern technologies require the development of new skills and changes in working patterns and relationships at all levels of the organization. Companies that invest in technology without investing in human capital development will not reach their full potential.
Keywords: technological advances; Brazil; human capital